Optimal decisions for capacitated supply shains with demand forecast updating - Zheng, Meimei (2015)
This thesis investigates how capacitated supply chains make decisions in face of high demand uncertainty. Delaying production or ordering decisions would provide demand responsiveness but incur additional costs and operational complexity. The tradeoffs between early and delayed decisions are investigated from the retailer’s, manufacturer’s and supply chain’s perspectives in three scenarios. In each scenario, optimal decisions are derived by mathematical analysis and be demonstrated to improve the performance. Meaningful managerial insights are provided by analytical and numerical results. Scenario 1 investigates an extension of the newsvendor with multiple ordering opportunities. To acquire more accurate demand forecast, a retailer prefers delaying order placement, which requires a shorter supply lead time. Due to limited capacity, the manufacturer would not only charge a higher cost for a shorter lead time but also set restrictions on the ordering times (or quantity) in supply mode A (or B). For supply mode A, it is proven under justifiable assumptions that the retailer should order either as early or as late as possible. For supply mode B, an algorithm is proposed to simplify the ordering policy by appropriately relaxing the ordering quantity restrictions. The value of demand forecast updating is illustrated by numerical analysis. Scenario 2 presents a two-stage newsvendor model, where an expensive emergency ordering opportunity with improved demand forecast and limited quantity is provided, besides the regular ordering opportunity. The optimal regular and emergency ordering quantities are derived by dynamic programming. The effects of the emergency order on the ordering decisions and expected profit are shown by numerical results. Scenario 3 studies how a supply chain utilizes a fast reactive production with improved demand information, whose quantity is limited by the preparation in advance. The condition under which adding the reactive production is valuable is derived. The condition is related to the demand forecast updating process, in addition to cost parameters. Furthermore, the benefit of this two-mode production system is illustrated by comparing it with two single production systems. In addition, an efficient pricing contract with a return policy is proposed and optimized to coordinate the supply chain. The coordination contract allows maximizing and arbitrarily allocating the supply chain profit, and remains the same when demand information is unknown to the manufacturer. The benefits of the two-mode production and values of coordination are demonstrated by numerical examples.